Investigation on Noise Characteristic of Cable Channel for Telemedicine - Jordanova, L.; Dimitrova, T. (Elektronika ir Elektrotechnika, 2009)
An investigation on noise characteristic of optic cable channel for telemedicine is described in the paper. Some application and development of optical systems Fiber to the Home (FTTH) have been done in the paper, also. The different kind of noise sources in FTTH systems are described , also. A computer method for restoration of frequency spectrum medical diagnostic signals is suggested in the paper. The restoration of frequency spectrum is as one development and application of mathematical method of Aizenberg in FTTH systems. Ill. 4, bibl. 5 (in English; summaries in English, Russian and Lithuanian).